Native Docker clustering with Swarm : deploy, configure, and run clusters of Docker containers with Swarm - Soppelsa, Fabrizio; Kaewkasi, Chanwit (Packt Publishing, 2016)
Deploy, configure, and run clusters of Docker containers with Swarm About This Book Get to grips with Docker Swarm, one of the key components of the Docker ecosystem. Optimize Swarm and SwarmKit features for scaling massive applications through containers. Learn about Docker's scheduling tricks, high availability, security, and platform scalability. Who This Book Is For If you are a Linux admin or a Docker user who wants to natively manage Docker clusters, then this is the book for you. What You Will Learn Create and manage Swarm Mode clusters of any size Get a backstage view of the biggest Swarms ever built : Swarm2k and Swarm3k, with their 2,300 and 4,700 nodes Discovery mechanisms and Raft Deploy your containerized app on Swarm Administer Swarm clusters on AWS, Azure, and DigitalOcean Integrate Flocker volumes with Swarm Create and manage Swarms on OpenStack Magnum In Detail Docker Swarm serves as one of the crucial components of the Docker ecosystem and offers a native solution for you to orchestrate containers. It's turning out to be one of the preferred choices for Docker clustering thanks to its recent improvements. This book covers Swarm, Swarm Mode, and SwarmKit. It gives you a guided tour on how Swarm works and how to work with Swarm. It describes how to set up local test installations and then moves to huge distributed infrastructures. You will be shown how Swarm works internally, what's new in Swarmkit, how to automate big Swarm deployments, and how to configure and operate a Swarm cluster on the public and private cloud. This book will teach you how to meet the challenge of deploying massive production-ready applications and a huge number of containers on Swarm. You'll also cover advanced topics that include volumes, scheduling, a Libnetwork deep dive, security, and platform scalability. Style and approach A comprehensive guide that covers all aspects of Docker Swarm from setup to customization.